Informed Consent for Surgery: Who is Consenting? - Kiyani, .ZiyadAfzal; Gilani, Irum (International Journal of Pathology, 2018)
AbstractObjective: To evaluate the awareness of informed consent among patients and current consent practices in ateaching hospital.Study Design: Cross-sectional Survey.Place and Duration: The study was carried out at Abbas Institute of Medical Sciences attached teachinghospital of AJK Medical College Muzaffarabad from February 2011 to April 2011.Materials and Methods: A closed ended questionnaire exploring the knowledge about informed consentwas administered to the patients post-operatively to study their awareness and the practices of informed consentin the hospital.Ethical approval: Ethical approval was taken from the hospital ethical committee. Informed consent wastaken from all the subjects and their identity was kept confidentialSample size: sample size was calculated by using WHO sample size estimatorResults: Out of ninety three respondents 59 (63.4%) were male and 34(36.6%) were female. Only 22 (23.7%)respondents gave consent of their surgery themselves for rest of 71 (76.3%) their attendants signed the consent fortheir patient’s surgery. 17 (28.8%) males and 12 (35.2%) females thought that they should have given consentthemselves.Conclusion:Patients, doctors and staff all are in a state of confusion that who should give consent; patient orattendants.Teaching ethics at undergraduate level will increase awareness in doctors; this will be a long termstrategy. As far as short term there is a dire need of developing protocols regarding informed consent at eachhospital level.